2009
DOI: 10.1128/aac.00433-09
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of dfrA and inhA Mutations to the Detection of Isoniazid-Resistant Mycobacterium tuberculosis Isolates

Abstract: Screening of 127 isoniazid (INH)-resistantMycobacterium tuberculosis isolates from Singapore for mutations within the dfrA and inhA genes revealed mutations in 0 and 5 (3.9%) isolates respectively, implying that mutations in dfrA do not contribute to the detection of INH-resistant M. tuberculosis and that mutations within inhA are rare. Thirty-seven (29%) of the 127 isolates had no mutations in any of the genes implicated in INH resistance (katG, kasA, and ndh; inhA and ahpC promoters), suggesting that there a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 27 publications
0
13
0
Order By: Relevance
“…Mutations in a number of other genes have been identified in INH-resistant M.tuberculosis strains (19) . However, approximately 22-29% of INH-resistant strains do not possess mutations in genes known to affect INHresistance (20) (21) , indicating that there may be unexplored mechanisms that influence INH efficacy in M.tuberculosis.…”
Section: Introductionmentioning
confidence: 99%
“…Mutations in a number of other genes have been identified in INH-resistant M.tuberculosis strains (19) . However, approximately 22-29% of INH-resistant strains do not possess mutations in genes known to affect INHresistance (20) (21) , indicating that there may be unexplored mechanisms that influence INH efficacy in M.tuberculosis.…”
Section: Introductionmentioning
confidence: 99%
“…A higher prevalence of mutations in katG (associated with a high level of INH resistance) than in the inhA/inhA promoter region (associated with a low level of INH resistance and coresistance to ETH) accounts for the fact that cross-resistance to the two drugs is not systematic in clinical strains, making the use of ETH in cases of INH resistance possible (30 (15). Few systematic studies on the distribution of nucleotide changes affecting the above-mentioned genes and focused primarily on a limited number of genes have been conducted (4,10,13,17,21,24).…”
mentioning
confidence: 99%
“…77 It was also recently suggested that mutations in dfrA play a role in resistance to isoniazid, 78 although other, more recent, studies have not corroborated this assertion. 79,80 Furthermore, mutations in thyA, which encodes thymidylate synthase, have been also suggested to confer resistance to trimethoprim/sulfamethoxazole. 81 Taking all this into consideration, and to better define the possible role of trimethoprim/sulfamethoxazole as a repositioned drug, adding to the anti-TB drug armamentarium, it will be Review 277 JAC necessary to further corroborate the few available studies that have reported activity of trimethoprim/sulfamethoxazole, or perhaps sulfamethoxazole alone, against a larger number of clinical isolates from different settings.…”
Section: Activity Of Trimethoprim/sulfamethoxazole Against Tbmentioning
confidence: 99%